2013
DOI: 10.1152/ajpgi.00472.2012
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic pathway of exogenous iron-loaded ferritin in intestinal epithelial (Caco-2) cells

Abstract: Artículo de publicación ISIFerritin, a food constituent of animal and vegetal origin, is a source of dietary iron. Its hollow central cavity has the capacity to store up to 4,500 atoms of iron, so its potential as an iron donor is advantageous to heme iron, present in animal meats and inorganic iron of mineral or vegetal origin. In intestinal cells, ferritin internalization by endocytosis results in the release of its iron into the cytosolic labile iron pool. The aim of this study was to characterize the endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
12
0
1
Order By: Relevance
“…Sonicated NP-FePO 4 (200) had a wide particle distribution (150–500 nm), therefore we hypothesize that the smaller particles may be absorbed using clathrin-mediated endocytosis and the larger particles using macropinocytosis. In recent reports, TEM micrographs of nanoparticle uptake have been observed for iron compounds from 10–100 nm size in Caco-2 cells [26,51,52]. Moreover, in support of our findings, a number of previous studies have shown that nano-sized iron compounds are absorbed using endocytic pathways in Caco-2 cells [22,23,26].…”
Section: Discussionsupporting
confidence: 91%
“…Sonicated NP-FePO 4 (200) had a wide particle distribution (150–500 nm), therefore we hypothesize that the smaller particles may be absorbed using clathrin-mediated endocytosis and the larger particles using macropinocytosis. In recent reports, TEM micrographs of nanoparticle uptake have been observed for iron compounds from 10–100 nm size in Caco-2 cells [26,51,52]. Moreover, in support of our findings, a number of previous studies have shown that nano-sized iron compounds are absorbed using endocytic pathways in Caco-2 cells [22,23,26].…”
Section: Discussionsupporting
confidence: 91%
“…Caco-2 monolayer model has been successfully applied to simulative absorption studies involving proteins, peptides, amino acids, and minerals. , To well establish the Caco-2 cell monolayers with enterocyte morphology to mimic in vitro calcium absorption, TEER values between apical and basolateral side of the monolayers were measured, as illustrated in Figure B. The TEER values increased as the incubation time was prolonged, and exceeded 400 Ω × cm 2 at day 12.…”
Section: Resultsmentioning
confidence: 99%
“…30 μg/dl difference in serum Fe levels between the FeNTA 2 ‐ and nanoFe 3+ ‐treated WT animals is mainly due to differences in the absorption kinetics of the two materials. Studies have shown that the rate of absorption of Fe from ferritin, which contains an Fe 3+ oxohydroxide core very similar to nanoFe 3+ and is taken up by clathrin‐dependent endocytosis (4749), is slower than that of soluble Fe in the rat intestine (50). Moreover, our own observations in human volunteers comparing nanoFe 3+ to FeSO 4 support this difference in kinetics (unpublished results).…”
Section: Discussionmentioning
confidence: 99%